Computational screening of coumarin derivatives as inhibitors of the NACHT domain of NLRP3 inflammasome for the treatment of Alzheimer’s disease - Ghosh P.; Singh R.; Chatterjee C.; Kumar A.; Singh S.K. (My University, 2025)
The nucleotide-binding oligomerization domain (NOD)-like receptor (NLR), leucine-rich-repeat (LRR), and pyrin domain containing 3 (NLRP3) is one of the key players in neuroinflammation, which is a major pathological hallmark of Alzheimer’s Disease (AD). Activated NLRP3 causes release of pro-inflammatory molecules that aggravate neurodegeneration. Thus, pharmacologically inhibiting the NLRP3 inflammasome has the potential to alleviate the inflammatory injury to the neurons. Coumarin is a multifunctional nucleus with potent anti-inflammatory properties and can be utilized to develop novel drugs for the treatment and management of AD. In the present study, we have explored the NLRP3-inhibitory activities of a library of coumarin derivatives through a computational drug discovery approach. Drug-like, PAINS free, and potentially BBB permeable compounds were screened out and subjected to molecular docking and in silico ADMET studies, resulting in three virtual hits, i.e. MolPort-050-872-358, MolPort-050-884-068, and MolPort-051-135-630. The hits exhibited better NLRP3-binding affinity than MCC950, a selective inhibitor of NLRP3. Further, molecular dynamics (MD) simulations, post-MD simulation analyses, and binding free energy calculations of the hits established their potential as promising virtual leads with a common coumarin scaffold for the inhibition of NLRP3 inflammasome. © 2023 Informa UK Limited, trading as Taylor & Francis Group.